The Role of Urban Farming in Improving Community Welfare and Urban Food Security: Case Study of Farmers Group of Giwangan Village, Yogyakarta City - Laksmi Yustika Devi; Latri Wihastuti; Marsyella Tri Ariyani; Meilani Putri Insani; Fidya Sekar Kinanti (Jurusan Ilmu Ekonomi dan Studi Pembangunan Universitas Jenderal Soedirman, 2023)
In many developing countries, the process of urbanization goes hand in hand with increasing urban poverty, food insufficiency and malnutrition, as well as rising unemployment rates. These urban problems are also found in the city of Yogyakarta. Therefore, since 2018, the City Government of Yogyakarta has initiated urban farming activities as a manifestation of efforts to create independent food security by the community. The urban farming activity is carried out on a micro scale through the role of farmer groups as evidenced by the growing number of small-scale farmer groups, namely the village level. Previous studies on urban farming have focused on obtaining quantitative data so that an assessment of the environmental, economic and social impacts of these activities can be carried out. This study also has the same focus with specific objectives, namely: 1) identifying the socio-economic profile of urban farming actors in Giwangan Village, Yogyakarta City and 2) identifying the role of urban farming in efforts to improve community welfare and urban food security in Giwangan Village, Yogyakarta City. The results show that respondents were engaged in urban farming as a hobby/recreation (26.7 percent) and to increase income (26.7 percent). Most of respondents get income from the sale of urban farming of less than 1 million Rupiah per month. Most of respondents (83.3 percent) considered that their urban farming activity was successful because it was able to reduce family’s food expenditures.Keywords: City of Yogyakarta, Urban Farming, Food Security, Public Welfare